2000
DOI: 10.1145/505680.505682
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fractional gaussian noise using linear approximation for generating self-similar network traffic

Abstract: The present paper focuses on self-similar network traffic generation. Network traffic modeling studies the generation of synthetic sequences. The generated sequences must have similar features to the measured traffic. Exact methods for generating self-similar sequences are not appropriate for long traces. Our main objective in the present paper is to improve the efficiency of Paxson's method for synthesizing self-similar network traffic. Paxson's method uses a fast, approximate synthesis for the power spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 18 publications
(65 reference statements)
0
24
0
1
Order By: Relevance
“…Following the notation of (3), Ledesma and Liu (2000) showed that it is possible to get an accurate approximation by keeping the first two terms in Eq. (2).…”
Section: First-order Approximationmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the notation of (3), Ledesma and Liu (2000) showed that it is possible to get an accurate approximation by keeping the first two terms in Eq. (2).…”
Section: First-order Approximationmentioning
confidence: 99%
“…Using Leibnitz's rule to derive under the integral sign (Spiegel and Liu, 1998;Ledesma and Liu, 2000) we obtain…”
Section: First-order Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…We set up the simulation environment as illustrated in Fig.2. We assume that RTT is given by FGN(Fractional Gaussian Noise) [16] with mean and variance of 0.05 sec and 0.0015 sec 2 , respectively. FGN can provide a self-similar process according to Hurst parameter.…”
Section: Throughput Performancementioning
confidence: 99%